2011
DOI: 10.1111/j.1365-2966.2010.18071.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy groups and clouds in the local (z∼ 0.01) Universe

Abstract: We present an all-sky catalogue of 395 nearby galaxy groups revealed in the Local Supercluster and its surroundings. The groups and their associations are identified among 10 914 galaxies at |b| > 15 • with radial velocities V LG < 3500 km s −1 . Our group-finding algorithm requires the group members to be located inside their zero-velocity surface. Hereby, we assume that individual galaxy masses are proportional to their total K-band luminosities,The sample of our groups, where each group has n ≥ 4 members, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
254
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(267 citation statements)
references
References 80 publications
8
254
0
2
Order By: Relevance
“…Increasingly complete data have been recently gathered on the distribution and motions of galaxies and their systems in the Local Universe (LU) at redshifts up to z = 0.01−0.03 or distances 50-150 Mpc from us (Crook et al 2007(Crook et al , 2008Abate & Erdogdu 2009;Makarov & Karachentsev 2011). As a major result from these data, new estimates of the mean local matter (dark and baryonic) density ρ loc have been derived.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly complete data have been recently gathered on the distribution and motions of galaxies and their systems in the Local Universe (LU) at redshifts up to z = 0.01−0.03 or distances 50-150 Mpc from us (Crook et al 2007(Crook et al , 2008Abate & Erdogdu 2009;Makarov & Karachentsev 2011). As a major result from these data, new estimates of the mean local matter (dark and baryonic) density ρ loc have been derived.…”
Section: Introductionmentioning
confidence: 99%
“…The reported values depend on the methods of mass determination and algorithms of group identification and carry considerable uncertainty: Ω loc = 0.08−0.23, expressed in the units of the critical cosmological density ρ c = 0.92 × 10 −29 g cm −3 . Makarov & Karachentsev (2011) prefer the lowest local density values as the most reliable. Earlier independent estimates from galaxy groups gave also low values: 0.1 was reported by Vennik (1984), Tully (1987), and Magtesyan (1988), Karachentsev (2005) derives Ω loc 0.1 for a volume of 20 Mpc across.…”
Section: Introductionmentioning
confidence: 99%
“…5 (left-hand panel), we present the spatial distribution of the 166 cluster galaxies (blue filled circles) included in our catalogue, in comparison with 79 and 157 member galaxies from Tully et al (1996, black dots) and Karachentsev et al (2013, open red circles), respectively. In the case of the catalogue of Karachentsev et al (2013), based on the galaxy group catalogue of Makarov & Karachentsev (2011), they define the Ursa Major cluster consisting of seven galaxy subgroups: NGC 3769, NGC 3877, NGC 3992, NGC 4111, NGC 4157, NGC 4217, and NGC 4346 groups. From our 166 galaxies, 141 are also included in the seven groups of Karachentsev et al (2013).…”
Section: Comparison With Previous Cataloguesmentioning
confidence: 99%
“…Based on the Local Supercluster galaxy group catalogue of Makarov & Karachentsev (2011), which was constructed by an algorithm of the modified friend-of-friend method, Karachentsev et al (2013) have suggested that the Ursa Major cluster includes seven subgroups. In order to confirm the existence of subgroups, we carried out the Dressler−Shectman test (DS test; Dressler & Shectman 1988) which allows us to quantify the substructure in a galaxy cluster using the line-of-sight velocities and the projected distribution of galaxies.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Thus several other techniques for group and cluster extraction have been developed, well reviewed by Gal (2006) and recently applied by Yang et al (2005), Koester et al (2007), Yang et al (2007), Hao et al (2010), Makarov & Karachentsev (2011), Wen et al (2012), and Muñoz-Cuartas & Müller (2012). However, whether any method is more reliable than the others is still largely a matter of taste and debate (Old et al 2014).…”
Section: Introductionmentioning
confidence: 99%